Psychological Profile of Patients Presenting with Dermatological Complaints: A Cross-sectional Study - Ram H Malkani; Komal Parekh; Suman Karmakar; Maninder Singh Setia (Wolters Kluwer Medknow Publications, 2024)
Objectives: The study evaluates the psychological profile in patients presenting to a dermatological clinic in Mumbai, India. Materials and Methods: We evaluated anxiety, depression, stress, anger, body image, and relationships in 63 outpatients presenting with dermatological complaints. We used linear regression models for multivariate analyses for coefficient and 95% confidence intervals (CIs). Results: The mean age (standard deviation [SD]) was 37.4 (14.9) years; 30 (51%) were female and 31 (49%) were male. The common diagnoses were papulosquamous conditions (24%), acne (18%), hair fall (15%), pigmentary conditions (11%), pruritus (10%), and infection (8%). The mean anxiety (SD) score was highest in pigmentary conditions (11.6 [13.9]), depression (15.0 [5.0]) and posttraumatic stress scores (16.3 [25.6]) in pigmentary conditions, social phobia scores in allergy (21.8 [17.0]), and anger scores in acne (25.4 [6.3]). The mean (SD) family scores were lowest in pruritus (8.0 4.2]), body image in infection (3.6 [0.9]), and self-image in pigmentation (6.0 [2.3]). The mean social phobia scores were higher in allergy compared with acne (12.2, 95% CI: 1.6, 22.8, P = 0.02). Body image scores were lower in pruritus (−7.7, 95% CI: −14.5, −0.9, P = 0.03). Conclusion: The psychological parameters differ in various dermatological conditions; hence, a complete profile analysis will be beneficial for designing interventions in these patients.